Bathycopea (Isopoda: Sphaeromatidea: Ancinidae) from Japan, with descriptions of two new species and redescription of B. parallela Birstein - Shimomura, Mitchitaka (Zootaxa, 2008)
Two new species of Bathycopea Tattersall, 1905 are described from Japan. Bathycopea oculata sp. nov. differs from its congeners in having laterally rounded pleonite 1, well-developed eye lobes with 43–57 ommatidia, uropod about 4–4.7 times as long as wide, blunt and broadly rounded distal corner of carpus of pereopod 1, and the propodus of male pereopod 2 about 2.9 times as long as carpus. Bathycopea dicarina sp. nov. is distinctive in having pleotelson with two dorsal carinae and the merus and carpus of male pereopod 2 slightly longer than ischium. Bathycopea parallela Birstein, 1963 is redescribed using newly collected specimens from the region of the type locality. A key to species of the genus is provided.